A comprehensive analysis of waterwheel technologies for pico hydropower: Evolution, performance, and optimization strategies - Hj Md Basar, Mohd Farriz; Zulkarnain, Izzatie Akmal; Sopian, Kamaruzzaman (Iquz Galaxy Publisher, 2025)
Small-scale hydropower systems, particularly pico hydro, are emerging as viable and sustainable renewable energy solutions with significant potential for future power generation. These systems offer economic, social, and environmental benefits, making them ideal for rural electrification, especially in regions with low-head and low-flow water resources. Besides, pico hydro primarily relies on the natural flow of water to generate electricity, requiring minimal or zero water storage, thereby reducing environmental impact and preserving local ecosystems. This paper explores the design and development of an overshot waterwheel turbine specifically designed for pico hydro applications in areas with minimal water resources. A comprehensive review of existing waterwheel technologies, such as undershot, breast shot, pitch back, and overshot, is conducted to understand their historical evolution, fundamental working principles, system designs, and key components. The performance and application of these waterwheel types are analysed, along with the challenges associated with their real-world operation. Additionally, this research addresses critical issues related to waterwheel efficiency and operational limitations, highlighting areas for further improvement and innovation. By comparing different waterwheel designs, the study provides insights into optimizing turbine performance and proposes recommendations for enhancing efficiency, reliability and sustainability in low-resource hydropower applications, particularly in remote or off-grid areas with limited infrastructure access.